Strategi Pembelajaran Mata Pelajaran Matematika - Rosita, Apriati (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2019)
The aim of this research is to describing the implementation of learning strategy inmathematics subject in the fifth grade in MI Ya Bakii Kesugihan 01. The research type whichis used by this research is using field research with qualitative descriptive. The methodwhich is used to collect the data, they are observation, interview, and documentation. Thedata description in this research is to explain many kind of learning strategies in themathematics subject and the steps while teaching mathematics in the fifth A grade, theresearcher is using the data analysis which is covering data reduction, data presentation,and conclusion